THE INFLUENCE OF WORK VALUES AND ORGANIZATIONAL CULTURE ON MILLENIAL GENERATION EMPLOYEE ENGAGEMENT - Ryowa Sihombing; Liswandi Liswandi (Management and Leadership Study Programme, 2019)
In the coming years, there will be a generation that dominates workplaces around the world, called millennial. This research was conducted to find out how intrinsic work values, extrinsic work values and organizational culture as independent variables can affect employee engagement of millennial workers. The sample of this study was 110 workers in Cikarang. This research uses a quantitative design using multiple linear regression methodology. The analysis shows that organizational culture and extrinsic work value have a significant influence on employee engagement. intrinsic work values provide insignificant influence on employee engagement in millennial workers.